Stoking the Fires for Māori & Pacific Student Success in Psychology. Issue 1 (2nd January 2021) - Waiari, Danielle Amare Kahurangi; Lim, Wern Tje; Thomson-Baker, Aliesha Polly; Freestone, Maddison Kiri; Thompson, Shauney; Manuela, Sam; Mayeda, David; Purdy (Te Rarawa, Ngai Takoto), Suzanne; Le Grice (Ngāpuhi, Te Rarawa), Jade
ABSTRACT: This study investigates Māori (Indigenous people of New Zealand) and Pacific (people living in New Zealand who identify with Pacific Islands heritage) student success in Psychology at The University of Auckland, casting a net around the barriers and facilitators of academic learning to better understand and delineate pathways to transform the institutional environment, fostering conditions that allow undergraduate students to flourish and access culturally specific support. Located within a university context, our methodology was informed by kaupapa Māori research, involving six focus groups with Māori and Pacific undergraduate students ( n  = 29), and a collaborative approach to thematic analysis. Five key themes were identified: Resisting individualising pressures and embracing whanaungatanga, facilitating ako and vā, collaborative learning relationships, embracing Māori and Pacific expertise and knowledge systems, and recalibrating Māori and Pacific psychology pathways. This study is unique in its approach, being led by Māori, Pacific, and Indigenous students, foregrounding limitations and enhancers within a dominant monocultural institution. Suggestions for universities seeking to forge pathways that support Māori and Pacific student success without separating from their cultural identity are offered.